Phonetic Contrast Analysis of Indonesian and Arabic - Humaidi Humaidi; Achmad Hafsin (Sekolah Tinggi Agama Islam Syaichona Moh. Cholil Bangkalan, 2021)
There are several factors that cause challenges for non-Arabic speakers in learning Arabic, including non-linguistics and linguistics. These factors also affect Indonesian students who study Arabic as a foreign language. In general, Indonesian students have difficulty learning Arabic because of a number of differences between Indonesian as their first language (L1) and Arabic as the target language (L2) in almost all aspects of language. The L2 learning process that does not display its linguistic similarities in L1 creates an assumption among Arabic language learners in Indonesia that the language is difficult to learn. Therefore, this study aims to: (1) describe the phonetic similarities between Indonesian and Arabic; (2) describe the phonetic differences between Indonesian and Arabic; and (3) offer a formulation of Arabic learning patterns for Indonesian speakers learning Arabic to help them learn Arabic more easily. This study uses a comparative descriptive qualitative approach. The results of data analysis showed three findings; (1) There are 16 (sixteen) similar sounds of Indonesian and Arabic phonemes; (2) There are 7 (seven) Indonesian phonemes that are not in Arabic; and (3) There are 13 (thirteen) Arabic phonemes that are not in Indonesian. Based on these findings, it is recommended that Arabic teaching prioritize similar sounds in Indonesian and Arabic.